Determinantes de contabilidade, intenção empreendedora e capacidade de absorção individual no processo de sucessão familiar rural - Bernardi, Bruna (2024)
This research addresses a critical theme at the intersection of accounting, entrepreneurship, and family management in the rural context, specifically focusing on the determinants of accounting, entrepreneurial intention, and individual absorptive capacity in the rural family succession process. The study is driven by the growing importance of effective management in family rural properties, especially in the face of contemporary challenges in agribusiness and the need for planned succession to ensure the continuity and development of these properties. The general objective of the study was to highlight the determinants of accounting, entrepreneurial intention, and individual absorptive capacity in the rural family succession process. To achieve this objective, specific objectives were established, including describing accounting practices in the investigated properties, identifying the entrepreneurial intention and the individual absorptive capacity of participants, gathering the characteristics of family succession, and assessing the relationships between the dimensions of accounting, entrepreneurial intention, and individual absorptive capacity in the context of family succession. The theoretical foundation of the dissertation was anchored in fundamental concepts of rural accounting, entrepreneurial intention, individual absorptive capacity, and rural family succession. Theories such as the Theory of Relevance of Accounting Information, Absorptive Capacity Theory, Theory of Planned Behavior, and Theory of the Family Business Life Cycle were adopted to underpin the investigation. Methodologically, the applied study adopted a quantitative, descriptive, and survey approach. Data collection was carried out through questionnaires applied to rural producers in the western region of Rio Grande do Sul, reaching a total of 128 respondents. Data analysis involved techniques of descriptive statistics and structural equation modeling. The results showed that the entrepreneurial intention of producers and their capacity to absorb new knowledge and practices are fundamental for innovation and long-term sustainability of family rural properties. Moreover, the study pointed to the relevance of appropriate accounting practices as support for strategic decisions in the context of agribusiness. It is concluded that rural accounting is relevant not only as a management and control mechanism but also as an influencing factor, along with entrepreneurial intention, in the family succession process. The research contributes significantly to the literature in accounting sciences, by elucidating how accounting, entrepreneurial intention, and individual absorptive capacity interact and influence the succession process in family rural properties. The practical implications of the study are clear for rural managers, educators, and policymakers, highlighting the need to strengthen accounting and entrepreneurial competencies among potential successors, as well as fostering a culture of continuous learning and innovation. The findings offer a promising path for the continuity and development of family rural properties, which reinforces the importance of preparation and planning for succession.